Review on recent advances in adsorptive desulfurization - Saha, Biswajit; Vedachalam, Sundaramurthy; Dalai, Ajay K. (Fuel processing technology, 2021)
The challenges of hydrodesulfurization for desulfurizing the refractory sulfur compounds of petroleum fuels are prompting researchers to investigate the different non-conventional desulfurization techniques. Adsorptive desulfurization (ADS) is emerging as a low-cost alternative to ultra-deep hydrodesulfurization. In ADS, sulfur compounds are removed via physicochemical adsorption using a selective adsorbent. This review focuses on the latest development in ADS. Zeolite, metal oxide, metal-organic framework, mesoporous material, and carbon are assessed for desulfurization of the model and real feedstocks. The ADS performance of these materials can be improved by incorporating metals. Recent progress on improving the selectivity, stability, reusability is discussed. Depending on adsorbent surface chemical composition, sulfur molecules are removed through π complexation, acid-base, metal‑sulfur, and Van der Waals forces. The effects of process parameters, thermodynamics, and kinetics of ADS are also discussed. Selectivity is found to be a key challenge in ADS of real feedstocks due to competitive adsorption. The testing of adsorbents with real fuels is crucial for the commercialization of ADS. Developments of robust adsorbent with less expensive metals and ideal regeneration methods are needed to demonstrate the capabilities of ADS commercially. The search for a low-cost, and efficient ADS adsorbent is ongoing, and currently, its industrial adaptation is extremely limited. [Display omitted] •A brief review of various desulfurization technologies.•Review of adsorptive desulfurization (ADS) and its mechanisms, thermodynamics and kinetics.•Zeolite, metal oxide, metal-organic framework, mesoporous material, carbon, and clay are assessed for ADS.•Zeolite, metal oxide, metal-organic framework, mesoporous material, carbon, and clay are assessed for ADS.•The current status of ADS for desulfurization of real feedstocks is emphasized.•Further research to overcome the present obstacles of ADS of petroleum feedstocks is proposed.